Determinant Perception Ease of Use, Effectiveness and Risk on The Interest of Transacting Using Financial Technology (Fintech) in Medan City Community - Cut Nurul A’la; Andri Soemitra; Nurbaiti Nurbaiti; Ainun Mardhiah (Management Department Universitas Islam Negeri Sumatera Utara, 2020)
This study aims to determine the effect of perceived ease of use on interest in transacting using fintech, the effect of effectiveness on interest in transactions using fintech, the effect of risk on interest in transactions using fintech, and the effect of perceived ease of use, effectiveness and risk on interest in transactions using fintech collectively. The population in this study were the people of Medan City. The data used are primary data, namely by using a questionnaire filled out by respondents with a sample of 100 people. The analysis technique used in this research is using multiple linear regression test. The results showed that simultaneously, the perceived ease of use, effectiveness and risk had a significant and positive effect on transaction interest as indicated by the value of Fcount> Ftable of (22.458> 2.70) with a significance of 0.00. Thus, it can be concluded that Ho is rejected and Ha is accepted, which means that there is a significant influence jointly on the perception of ease of use, effectiveness and risk on the interest in transacting using Fintech in the people of Medan City.Keywords: Effectiveness, fintech, perceived ease of use, risk, transaction interest